2012
DOI: 10.1016/s1995-7645(12)60159-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on small ruminant lungworms and associated risk factors in northeastern Iran

Abstract: Due to its impact on production, emphasis should be given for the control and prevention of lungworm infection in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 4 publications
3
15
4
Order By: Relevance
“…The lungworm prevalence in Sidi Bouzid District was similar to those reported in Iran (10.8%; Borji et al, 2012) and in Spain (11.6%; López et al, 2011), but lower than those reported in Turkey (14%; Yildiz, 2006), in Morocco where the animals were infested by M. capillaris (35.5-70%) and D. filaria (5-30%) (Paliargues et al, 2007), and in Ethiopia (Addis et al, 2011) where a prevalence of 32.6% was observed. In this latter country, animals are reared in highlands where the climate is quite different: mean annual rainfall of 950-1750 mm and temperatures of 3-21.6°C.…”
Section: Infestation Prevalence According To Lungworm Speciessupporting
confidence: 84%
See 2 more Smart Citations
“…The lungworm prevalence in Sidi Bouzid District was similar to those reported in Iran (10.8%; Borji et al, 2012) and in Spain (11.6%; López et al, 2011), but lower than those reported in Turkey (14%; Yildiz, 2006), in Morocco where the animals were infested by M. capillaris (35.5-70%) and D. filaria (5-30%) (Paliargues et al, 2007), and in Ethiopia (Addis et al, 2011) where a prevalence of 32.6% was observed. In this latter country, animals are reared in highlands where the climate is quite different: mean annual rainfall of 950-1750 mm and temperatures of 3-21.6°C.…”
Section: Infestation Prevalence According To Lungworm Speciessupporting
confidence: 84%
“…The high density of sheep sharing common pastures, because extensive breeding systems are continuously used throughout the year, could also explain the high prevalence observed. Borji et al (2012) reported the presence in Iran of two lungworm species, D. filaria and P. rufescens. They showed that the infestation prevalence was significantly higher in young animals than in adult sheep (5.9% and 0.8%, respectively).…”
Section: Infestation Prevalence According To Lungworm Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned studies were conducted in the west and northeast part of Ethiopia while the present study was carried out in the southern part. Outside Ethiopia, surveys in Turkey, India and Iran [21][22][23][24][25] also reported D. filaria as the sole or predominant lungworm while in Morocco, Czech Republic, Norway and Bulgaria the most prevalent species identified was M. capillaris [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…A number of bacterial, viral and parasitic agents participate in sheep respiratory diseases, however most important include: mycoplasma species such as Mycoplasma ovipneumoniae, Mycoplasma.arginini, Mycoplasma agalactiae (Lin et al, 2008), lung worms particularly (Dictyocaulus filaria) (Borji et al, 2012) and bacteria like Pasteurella multocida, Manhemia haemolytica, Chlamydia psittaci, Histophilus somni, which can suppress the animal's immune system, allowing opportunistic microorganisms to colonize the lung and cause the disease (Angen et al,1998;Radostits et al, 2000;Tesfaye et al, 2013;Fulton, 2009;Alemneh and Tewodros, 2016).…”
Section: Introductionmentioning
confidence: 99%